DETERMINAN AKUNTABILITAS KINERJA ORGANISASI PERANGKAT DAERAH KOTA PALEMBANG - Prameswari, Fathia Andina; Rachma Sari, Kartika; Sarikadarwati (Jurnal Riset Terapan Akuntansi, 2024)
The purpose of the study was to determine organizational commitment, human resource capabilities, budget appraisal and budget target clarity affect the performance accountability of Regional Organizations (OPD) in Palembang City in 2024, totaling 32 OPDs. This study uses saturated sampling sample collection techniques. Data analysis using multiple linear regression using raw data and data hypothesis testing tools with Statistical Products and Services Solutions (SPSS) software version 26. The results of several hypothesis tests show that the variables that have a positive and significant influence on OPD performance accountability in Palembang City are: organizational commitment, human resource capabilities, and clarity of budget targets. The results of hypothesis testing in this study are simultaneously similar. The conclusion of this study shows that organizational commitment, human resource capabilities, and clarity of budget objectives together have a significant and positive influence on OPD performance accountability in Palembang City. Keywords: Organizational Commitment, Human Resources Competency, Clarity of Budget Targets.